Change in the Andes : origins of social complexity, pastorilism and agriculture ; Sessions générales = General Sessions - (:unkn) unknown (Archaeopress, 2006)
The goal of this colloquium is to discuss several problems to the economic and social changes occrred in the Andean Area through the Holocene. These changes involved certain aspects of the social trajectories in the different andean regions coupled with a set of changing social and enviromental conditions in space and time. These processes could be studied from a regional perspective, but also have general elements that permits integrate knowledge of different sectors of the Andes from Ecuador to Chile and Argentina. We suggest the following topical items for the discussion: 1. Relationship between enviromental, economical and social changes 2. Social complexity in hunter-gatherers 3. Origins of camelid pastoralism 4. Origins of agriculture 5. Political power, hierarquical and social stratification in the Andean societies Social meaning of the Anden simbolic world
Ponencia presentada en el XIV UISPP Congress, celebrado en University of Liège, Bélgica, entre el 2 y 8 se septiembre de 2001. Section 17, Préhistoire de l'Amérique = American prehistory, C17.1.
La versión digital aún no está disponible.
Keywords: Arqueología